HO-1 Upregulation Attenuates Adipocyte Dysfunction, Obesity, and Isoprostane Levels in Mice Fed High Fructose Diets - Zeid Khitan; Mohit Harsh; Komal Sodhi; Joseph I. Shapiro; Nader G. Abraham (Journal of Nutrition and Metabolism)
Background. Fructose metabolism is an unregulated metabolic pathway and excessive fructose consumption is known to activate ROS. HO-1 is a potent antioxidant gene that plays a key role in decreasing ROS and isoprostanes. We examined whether the fructose-mediated increase in adipocyte dysfunction involves an increase in isoprostanes and that pharmacological induction of HO-1 would decrease both isoprostane levels and adipogenesis. Methods and Results. We examined the effect of fructose, on adipogenesis in human MSCs in the presence and absence of CoPP, an inducer of HO-1. Fructose increased adipogenesis and the number of large lipid droplets while decreasing the number of small lipid droplets (P<0.05). Levels of heme and isoprostane in fructose treated MSC-derived adipocytes were increased. CoPP reversed these effects and markedly increased HO-1 and the Wnt signaling pathway. The high fructose diet increased heme levels in adipose tissue and increased circulating isoprostane levels (P<0.05 versus control). Fructose diets decreased HO-1 and adiponectin levels in adipose tissue. Induction of HO-1 by CoPP decreased isoprostane synthesis (P<0.05 versus fructose). Conclusion. Fructose treatment resulted in increased isoprostane production and adipocyte dysfunction, which was reversed by the increased expression of HO-1.